2019
DOI: 10.1111/cwe.12298
|View full text |Cite
|
Sign up to set email alerts
|

Zombie Firms and Debt Accumulation: A Theoretical Framework and Chinese Experience

Abstract: In recent years, as China has grappled with rising debt and broad economic restructure, the prevalence of zombie firms has become a critical problem. This paper provides a theoretical framework illustrating the rationale behind the occurrence of zombie firms from the perspective of banks. We develop differential equations to model a bank's expectation and the ex ante estimate that underlies its decision to refinance an insolvent borrower. An optimistic expectation is essential in zombie lending and is intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…(ii) Bank loans are a pre-existing behavior, and the formation of zombie firms is an after-event behavior. The pre-existing banks' overly optimistic expectations of corporate profits have caused zombie firms (Zhu et al 2019). (iii) Regulatory forbearance towards banks may lead to an increase in zombie lending practices (Chari et al 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(ii) Bank loans are a pre-existing behavior, and the formation of zombie firms is an after-event behavior. The pre-existing banks' overly optimistic expectations of corporate profits have caused zombie firms (Zhu et al 2019). (iii) Regulatory forbearance towards banks may lead to an increase in zombie lending practices (Chari et al 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chinese scholars proposed a further improved method based on the fact that government intervention is the most important reason for the formation of zombie firms in China, adding the factor of government subsidies to the FN‐CHK method (X. Y. Dai et al, 2019; Huang & Chen, 2017; Y. Q. Wang & Zhu, 2020). For the causes of zombie firms' formation, most scholars believe that the continuous ‘blood transfusion’ of banks to zombie firms is the main reason for the formation of zombie firms (Fukuda et al, 2006; Hoshi & Kashyap, 2011; Peek & Rosengren, 2005; Watanabe, 2011; Zhu et al, 2019). On the contrary, Chinese scholars found that a combination of market and policy factors is the main reason for such formation in China (He & Zhu, 2016).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Wang & Zhu, 2020). For the causes of zombie firms' formation, most scholars believe that the continuous 'blood transfusion' of banks to zombie firms is the main reason for the formation of zombie firms (Fukuda et al, 2006;Hoshi & Kashyap, 2011;Peek & Rosengren, 2005;Watanabe, 2011;Zhu et al, 2019). On the contrary, Chinese scholars found that a combination of market and policy factors is the main reason for such formation in China (He & Zhu, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, Ogawa and Kitasaka (2000) and Giannetti and Simonov (2013) propose an alternative explanation: lending to firms in need enables banks to maintain good customer relationships and networks. That is, lending to zombie firms can be an "optimal strategy" to the banks, especially in Japan when there is a close bank-firm relationship (Jaskowski 2015; Bergant and Kockerols 2020; Zhu et al 2019).…”
Section: Why Does Zombie Lending Happen?mentioning
confidence: 99%
“…They find that credit misallocation might not have any significant impacts on the growth of healthy firms and TFP after addressing the deficiencies from the original model. In addition, empirical evidence from Japan, China, and Europe has all shown that most zombie firms left the market voluntarily; furthermore, most of those that stayed became profitable again shortly after the economy recovered (Fukuda and Nakamura 2011;Zhu et al 2019; Banerjee and Hofmann 2020; Goto and Wilbur 2019). Therefore, while zombie lending is costly in the long run and should be avoided, it appears to be the case that zombie lending can be temporary financial help to viable firms.…”
Section: Economic Consequences Of Zombie Lendingmentioning
confidence: 99%